Analysis of the Entrapment Efficiency of Thymoquinone in Microcapsules of Black Cumin Seed Oil (Nigella sativa L.) Using High Performance Liquid Chromatography - Ofa Suzanti Betha; Supandi, Supandi; Addina Syahida; Boy Reynaldi Noor; Nelly Suryani; Sabrina Dahlizar; Yuni Anggraeni; Barita J. Siregar; Zilhadia (Journal of Fundamental and Applied Pharmaceutical Science, 2025)
Thymoquinone is the main active compound found in black cumin seed oil (Nigella sativa). This study intends to analyze the efficiency of its absorption in microcapsules by the ionic gelation of cross-linked alginate and the CaCl2 method, and loading with black cumin seed oil in a concentration of 20%. Thymoquinone was used as a marker to establish quality standards for this microcapsule preparation. Analysis of thymoquinone in microcapsules was performed using a pre-optimized, high-performance liquid chromatography method. Method optimization utilized an Acclaim® Polar Advantage II (C18) column with a flow speed of 1.5 mL/min, a UV detector wavelength of 252 nm, and an injection volume of 20 μL with an isocratic system on a methanol eluent composition: water (70:30). This method revealed a good linearity value (r = 0.9997) in the range of 0.5 – 500 μg/ml. The detection and quantitation limits were 8.67 μg/mL and 28.9 μg/mL, (%diff) was about -1.864 to 1.562, precision (% RSD) was 0.052 to 0.113%, and the recovery was 98.135 to 101.563%. The results of this method validation were then applied to determine thymoquinone loading in black cumin seed oil microcapsules. The results of the absorption efficiency value of black cumin seed oil microcapsules by the ionic gelation alginate and CaCl2 method, which contained 20% oil concentration in the formula, were 81.769%.